Chromium (III) doped polycrystalline MgAl2O4 nanoparticles for photocatalytic and supercapacitor applications. (February 2022) - Alam, Mir Waqas; Kumar, V.G. Dileep; Ravikumar, C.R.; Prashantha, S.C.; Murthy, H.C. Ananda; Kumar, M.R. Anil
Abstract: A significant increase in demand for non-conventional energy sources has occurred recently. The most promising and dependent energy storage devices are supercapacitors. The mixed metal oxide MgAl2 O4 has appreciable dielectric behavior but its application as an electroactive material is limited due to its low conductivity. In the present work, we demonstrated the exceptional supercapacitor application of doped MgAl2 O4 . Chromium (Cr 3+ )-doped (5 mol%) MgAl2 O4 nanoparticles (NPs) were synthesized by solution combustion method. The morphological and structural features of the synthesized NPs were confirmed by the application of modern techniques. The Cr 3+ -doped MgAl2 O4 NPs showed excellent photocatalytic activity against Acid Red-88 (AR-88) dye, with 89.2% degradation compared to 77.5% for undoped MgAl2 O4 . The electrochemical activity of Cr 3+ -doped MgAl2 O4 NPs over the undoped counterpart was compared using cyclic voltammetric and electrochemical impedance spectroscopic measurements in an alkaline medium. The positive impact of Cr 3+ on the conductivity and electrochemical activity of MgAl2 O4 was evident with the attainment of higher specific capacitance value of 955.3 F g −1 at 1 A g −1 current density compared to 816.8 F g −1 for undoped MgAl2 O4, and a high cycle life of over 2000 cycles. We report the superior electrochemical behavior of Cr 3+ -doped MgAl2 O4 as anodic material for supercapacitor applications compared to undoped MgAl2 O4 . In addition, the synthesized Cr 3+ -doped MgAl2 O4 NPs exhibited 89.2% degradation efficiency against AR-88. Highlights: Chromium (Cr 3+ )-doped (5 mol%) MgAl2 O4 nanoparticles (NPs) used to degrade AR-88 dye. Cr 3+ -doped MgAl2 O4 NPs showed 89.2% dye degradation. Positive impact of Cr 3+ on the conductivity and electrochemical activity of MgAl2 O4 . Excellent anodic material for supercapacitor applications.